PENGARUH RELIGIUSITAS, REPUTASI, DAN LOKASI TERHADAP KEPUTUSAN MENABUNG PADA PERBANKAN SYARIAH DI JAKARTA - Radja Rabbani Mahesazzumar (2021)
Islamic banking is currently growing quite rapidly and continues to experience positive growth in recent times. Although the development is very rapid, it is still quite difficult for Islamic banking to compete with conventional banking. This study aimed to determine and analyze the effect of the variables religiosity, reputation, and location on the decision to save in Islamic banking, especially in Jakarta. The data collection technique used a purposive sampling technique with respondents totaling 91 Islamic bank customers. The data analysis technique with SmartPLS 3.2 software. The results of this study, namely: (1) The religiosity variable has an insignificantly affects the saving decision, (2) the reputation variable has a significant effect on the saving decision, and (3) the location variable has a significant effect on the saving decision. The limitations of this study where the researcher only uses three independent variables and is relatively small because it is only in Jakarta. Hopefully this research will be useful for Islamic banking to take action continue fpr improve the reputation and increase the distribution of bank locations, and the government can make policies that focus on developments in Islamic banking. Keywords: location, religiosity, reputation